Mental Health in Later Life: Clinical Challenges, Social Determinants, and Multilevel Responses in an Ageing World, with Evidence from India - Vijaya Upadhyay; Satyendra Mani Vikram (Journal of Education, Society and Behavioural Science, 2026)
Population ageing is changing the epidemiology, clinical presentation and service requirements of mental disorders. Later-life mental health cannot be understood solely as a set of psychiatric diagnoses because depressive and anxiety disorders, neurocognitive disorders, sleep disturbance, grief, substance-related problems and suicidal behaviour interact with multimorbidity, disability, sensory loss, polypharmacy and social adversity. This critical narrative review integrates international evidence with a specific examination of India, where demographic ageing is accelerating while family structures, labour migration, social protection and health-service capacity are changing. Literature published from 2000 to 26 June 2026 was prioritised, with earlier seminal and methodological sources retained where necessary. Evidence was identified through PubMed, Europe PMC, Google Scholar, DOAJ, Semantic Scholar, WHO Global Index Medicus/IMSEAR-oriented searches, Crossref verification, citation chaining and authoritative institutional sources. The evidence indicates that later-life mental health outcomes are socially patterned: poverty, widowhood, living alone, loneliness, elder abuse, functional limitation, sensory impairment, neighbourhood insecurity and ageism often cluster, while protective social participation and access to integrated care remain uneven. Indian analyses based largely on the Longitudinal Ageing Study in India provide nationally important associations but are predominantly cross-sectional, creating a recurrent gap between epidemiological description and causal inference. Clinically, under-recognition is reinforced by somatic presentation, cognitive overlap, stigma and fragmentation between geriatric, neurological, primary-care and psychiatric services. Effective responses therefore require multilevel action: age-sensitive primary care and collaborative mental-health pathways, attention to cognition and function, caregiver support, social-connection interventions, protection from abuse, income and housing security, accessible transport and digital inclusion. The central conclusion is that late-life mental health should be treated as a combined clinical, social and systems problem. India has a strong empirical platform for action, but longitudinal, intervention and implementation evidence must now catch up with the speed of demographic change.